2007
DOI: 10.5650/jos.56.347
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Effect and Safety of Dietary .ALPHA.-Linolenic Acid in Subjects with High-Normal Blood Pressure and Mild Hypertension

Abstract: We investigated the antihypertensive effect and safety of a-linolenic acid (ALA) in human subjects. In Experiment 1, subjects with high-normal blood pressure and mild hypertension ingested bread containing 14 g of common blended oil (control oil) or ALA-enriched oil for 12 weeks. The test oil contained 2.6g/14 g of ALA. The subjects ingested strictly controlled meals during the study period. Systolic blood pressure was significantly lower in the ALA group than in the control group after ingestion of the test d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 27 publications
2
34
2
3
Order By: Relevance
“…Some epidemiological studies have also demonstrated that dietary intake of ALA is inversely associated with blood pressure [12][13][14][15] . Recently, we showed that a diet supplemented with ALA lowered systolic blood pressure (SBP) and diastolic blood pressure after 12 weeks in Japanese subjects with high-normal blood pressure and mild hypertension 16) . However, the antihypertensive mechanism of ALA is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Some epidemiological studies have also demonstrated that dietary intake of ALA is inversely associated with blood pressure [12][13][14][15] . Recently, we showed that a diet supplemented with ALA lowered systolic blood pressure (SBP) and diastolic blood pressure after 12 weeks in Japanese subjects with high-normal blood pressure and mild hypertension 16) . However, the antihypertensive mechanism of ALA is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…N-3 polyunsaturated fatty acids (PUFAs), such as α-linolenic acid, eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA), have been attracting attention regarding their preventive effects against diseases such as atherosclerosis, coronary arterial heart diseases, and hypertension (Conner, 2000;Takeuchi et al, 2007). N-3 PUFAs are easily oxidized because they contain many double bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Some epidermal studies have also demonstrated that dietary intake of ALA is inversely associated with blood pressure [16][17][18][19] . Recently, we showed that a diet supplemented with ALA lowered systolic blood pressure (SBP) and diastolic blood pressure (DBP) after 12 weeks in Japanese subjects with high-normal blood pressure and mild hypertension 20) . However, the antihypertensive mechanism of ALA is not fully understood.…”
Section: Introductionmentioning
confidence: 99%